Addressing learner diversity by culturally responsive pedagogy - Tengku Nor Rizan Tengku Mohamad Maasum,; Nooreiny Maarof,; Manisah Mohd Ali, (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2015)
Malaysian school classrooms are characterized by its diversity whereby students (Malay Chinese, Indian and other ethnic groups) come from various cultural backgrounds. Studies have shown that culture influences the learning process and social adjustment of students. Providing culturally appropriate practice is one of the main concerns of the teaching profession. To do that teachers need to be able to promote cultural understanding to enable students to become sensitive to other students from other cultures and to eventually be able to live harmoniously in a multicultural community. They need to be multi-culturally aware of differences among students to better act as role models in classroom. The objective of this paper is to describe the effect of a multicultural competence workshop in raising a group of 128 primary school teachers’ awareness about multiculturalism in the classroom. Multicultural competence comprises multicultural awareness (how people’s attitudes, beliefs, values, assumptions, self-awareness affect the ways they interact with those who are culturally different from themselves), knowledge (informed understanding of cultures that are different from one’s own culture) and skills (skills individuals use to engage in effective and meaningful interactions with those who are from different cultural backgrounds). The training workshop employs three main activities (a) self-awareness, (b) awareness of Malaysian cultures and (c) instructional strategies and resources. The qualitative data reveals that the teachers find that the workshop activities to be supportive of a culturally responsive pedagogy. These activities have helped them to be aware of their own thinking, biases and emotions towards diversity in the classroom. The activities of the workshop seem to have been facilitative in increasing the teachers’ multicultural awareness and competency. It can be concluded that the teachers have positive responses to the workshop. The study indicates that teachers need to be exposed to multicultural activities that could assist them in implementing a culturally-responsive pedagogy.